Opportunities and Challenges of Online Exit Exams in Higher Education: A Systematic Review - Teshome, Samson Worku (ALSYSTECH Journal of Education Technology, 2025)
This systematic review investigates the opportunities and challenges of online exit exams in higher education, employing the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework and PICO (Population, Intervention, Comparison, Outcome) model to ensure methodological rigor. The review synthesizes findings from 34 studies spanning 1994 to 2024, covering diverse geographic regions including Europe, North America, Africa, Asia, and Australia. The studies utilized a range of methodologies, including descriptive case studies, literature reviews, empirical research, policy analyses, and quantitative investigations, providing a comprehensive understanding of the impact of online exit exams on educational quality, teaching practices, and student outcomes. Key opportunities identified include enhanced accessibility for remote learners, cost-efficiency through reduced logistical demands, data-driven improvements via analytics, flexibility for diverse student needs, and standardized testing frameworks. However, significant challenges persist, such as the digital divide, concerns about academic integrity, technical reliability issues, limitations in assessing practical skills, and psychological stress among students. A comparative analysis reveals complex interrelationships between these themes, highlighting tensions between accessibility and equity, cost-efficiency and security, and standardization and cultural relevance. The review underscores the need for robust technical infrastructure, faculty training, and adaptive strategies to balance rigorous assessment standards with equitable practices. Future research should prioritize globally representative studies addressing gaps such as publication bias and exclusion of non-English literature, while exploring intersections of technological readiness, institutional culture, and socio-economic factors.